2012
DOI: 10.1111/j.1476-5381.2012.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐(1–7) inhibits allergic inflammation, via the MAS1 receptor, through suppression of ERK1/2‐ and NF‐κB‐dependent pathways

Abstract: BACKGROUND AND PURPOSEAngiotensin-(1-7) [Ang-(1-7)] has anti-inflammatory effects in models of cardiovascular disease and arthritis, but its effects in asthma are unknown. We investigated whether Ang-(1-7) has anti-inflammatory actions in a murine model of asthma. EXPERIMENTAL APPROACHThe effects of Ang-(1-7) alone or in combination with the MAS1 receptor antagonist, A779, were evaluated over a 4 day period in an ovalbumin-challenged mouse model of allergic asthma. On day 5, bronchoalveolar lavage was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 42 publications
10
115
0
5
Order By: Relevance
“…22 Treatment with Ang-(1-7) alleviated inflammation via regulation of the extracellular signal regulated kinase, one of the MAPK family members, and NF-jB pathways in an allergic asthma mouse model. 67 In line with our previous studies, activation of the ACE2/Ang-(1-7)/Mas axis downregulated phosphorylation of MAPKs and NF-jB signaling. 33,36 These data indicated that ACE2 may ameliorate the inflammatory response by regulating MAPKs and NF-jB pathways.…”
Section: Ace2 Reduces Ab-induced Inflammation In Human Rpesupporting
confidence: 76%
“…22 Treatment with Ang-(1-7) alleviated inflammation via regulation of the extracellular signal regulated kinase, one of the MAPK family members, and NF-jB pathways in an allergic asthma mouse model. 67 In line with our previous studies, activation of the ACE2/Ang-(1-7)/Mas axis downregulated phosphorylation of MAPKs and NF-jB signaling. 33,36 These data indicated that ACE2 may ameliorate the inflammatory response by regulating MAPKs and NF-jB pathways.…”
Section: Ace2 Reduces Ab-induced Inflammation In Human Rpesupporting
confidence: 76%
“…Therefore, the increase of antigen-presenting cell migration into atherosclerotic plaques as well as the enhanced plaque size, which we observed in our ApoEKO mouse model, may be mediated by an effect of Mas on chemokine expression. Well in line with this observation, Mas deficiency enhances the expression of the chemokine CCL2 in vitro and in vivo with NF-κB as a key regulator (30,31).…”
Section: Discussionmentioning
confidence: 66%
“…5 μm thick sections were stained with hematoxylin and eosin (H & E) and examined for pathological changes under light microscopy (El-Hashim et al, 2012).…”
Section: Airway and Heart Histologymentioning
confidence: 99%